Discovery of VU6015929: A Selective Discoidin Domain Receptor 1/2 (DDR1/2) Inhibitor to Explore the Role of DDR1 in Antifibrotic Therapy - Jeffries, Daniel E. (ACS Med Chem Lett, 2019)
[Image: see text] Herein, we report the discovery of a potent and selective dual DDR1/2 inhibitor, 7e (VU6015929), displaying low cytotoxicity, good kinome selectivity, and possessing an acceptable in vitro DMPK profile with good rodent in vivo pharmacokinetics. VU6015929 potently blocks collagen-induced DDR1 activation and collagen-IV production, suggesting DDR1 inhibition as an exciting target for antifibrotic therapy.